The utility of heart failure registries: a descriptive and comparative study of two heart failure registries. Issue 1087 (6th January 2016) - Trullàs, Joan Carles; Miró, Òscar; Formiga, Francesc; Martín-Sánchez, Francisco Javier; Montero-Pérez-Barquero, Manuel; Jacob, Javier; Quirós-López, Raúl; Herrero Puente, Pablo; Manzano, Luís; Llorens, Pere; ,
Abstract: Background and aim: Registries are useful to address questions that are difficult to answer in clinical trials. The objective of this study was to describe and compare two heart failure (HF) cohorts from two Spanish HF registries. Methods: We compared the RICA and EAHFE registries, both of which are prospective multicentre cohort studies including patients with decompensated HF consecutively admitted to internal medicine wards (RICA) or attending the emergency department (EAHFE). From the latter registry we only included patients who were admitted to internal medicine wards. Results: A total of 5137 patients admitted to internal medicine wards were analysed (RICA: 3287 patients; EAHFE: 1850 patients). Both registries included elderly patients (RICA: mean (SD) age 79 (9) years; EAHFE: mean (SD) age 81 (9) years), with a slight predominance of female gender (52% and 58%, respectively, in the RICA and EAHFE registries) and with a high proportion of patients with preserved ejection fraction (58% and 62%, respectively). Some differences in comorbidities were noted, with diabetes mellitus, dyslipidaemia, chronic renal failure and atrial fibrillation being more frequent in the RICA registry while cognitive and functional impairment predominated in the EAHFE registry. The 30-day mortality after discharge was 3.4% in the RICA registry and 4.8% in the EAHFE registry (p<0.05) and the 30-day readmission rate was 7.5% in the RICA registry (readmission to hospital) and 24.0% in the EAHFE registry (readmission to emergency department) (p<0.001). Conclusions: We found differences in the clinical characteristics of patients admitted to Spanish internal medicine wards for decompensated HF depending on inclusion in either the RICA or EAHFE registry.